Integrated management of Colletotrichum gloesporioides in yellow passion fruit (Passiflora edulis f. flavicarpa Degener) - Campo-Arana, Rodrigo Orlando; Urango-Esquivel, Naudith; Pérez-Polo, Dairo (Revista de Ciencias Agrícolas, 2019)
Anthracnose (Colletotrichum gloeosporioides) is one of the most limiting diseases of yellow passion fruit, reducing crop production by more than 80%. This research aimed to assess anthracnose management strategies on yellow passion fruit crop sanitation and yield. We assessed the effect of alternating fungicide applications (//) every 15 days with foliar nutrients on the severity of anthracnose and crop yield in a commercial crop in San Isidro district (Montería), located at coordinates 8°44'52.7'' N, 75°52'53.2''W and 75m.a.s.l. We conducted this research in two experiments; in the first, we assessed the response of the disease index (DI) after the application of the following treatments: T1=Manazeb (Mancozeb) // Potassium phosphite (Foscrop), T2=Mancozeb // Potassium (Terramin potassium), T3=Mancozeb // Calcium (Terramin calcium), T4=Trichoderma spp. (Fitotripen) // Copper oxychloride, T5=Azoxystrobin (Amistar) // Mancozeb, and T6=Control sprayed with water. In the second experiment, we selected the best treatments, as follows: T1 = Amistar // Mancozeb; T2 = Terramin potassium // Mancozeb, and T3 = Control. We evaluated DI, percent of affected fruits, number of fruits/ha, and yield (Kg/ha). The results from the first experiment showed that T1 and T5 controlled anthracnose, reducing the levels of severity by 39.69% compared to the control (T6). In the second experiment, T1 decreased the levels of foliage severity by 29.04% and increased the number of fruits/ha and yield by 200% compared to the control. Overall, the fungicide application of Azoxistrobin alternating with Manazeb constitutes an effective alternative to control anthracnose in yellow passion fruit cultivation.